FAKTOR - FAKTOR YANG MEMPENGARUHI MINAT PERILAKU WAJIB PAJAK ORANG PRIBADI DALAM MENGGUNAKAN E-FILING DI KOTA SURAKARTA - Caroline Ayunita Vivi Pratiwi,; Nur Kholis, (Juremi: Jurnal Riset Ekonomi, 2022)
This research was carried out to find out what variables influenced WPOP's interest in e-filing in Surakarta City. Perceptions of convenience, perceptions of usefulness, readiness of information technology, and social factors are variables that are taken into account. A total of 363 WPOP recorded and active in the KPP Pratama Surakarta area identified respondents' answers to the questionnaire. The SPSS version 22 program is used to carry out descriptive statistical tests, validity tests, reliability tests, classical assumption tests, and hypothesis tests on questionnaire data. The conclusion of this study is that the behavioral implications of e-filing for WPOP are influenced by Perception of Ease (X1), Perception of Usability (X2), and Social Factors (X4), while Information Technology Readiness (X3) has no effect.